PENATALAKSANAAN HOLISTIK PADA WANITA USIA 54 TAHUN DENGAN HIPERTENSI, DM TIPE 2 DAN HIPERKOLESTEROLEMIA MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS KARANG ANYAR - Muhammad, Innou Dhanu; Saftarina, Fitria (Medula, 2024)
Hypertension is a condition when blood pressure in the blood vessels increases chronically. Data from the World Health Organization (WHO) in 2015 showed that the incidence of hypertension in the world reached 1.13 billion and in 2025 the number of hypertension sufferers will continue to increase to reach 1.5 billion individuals. Type 2 DM is a metabolic disease characterized by hyperglycemia due to insufficiency of insulin secretion by pancreatic beta cells or impaired insulin function. According to the International Diabetes Federation (IDF), it is estimated that one in 11 adults or 90 million people (aged 20-79 years) in Southeast Asia will suffer from DM in 2021. Hypercholesterolemia is a condition characterized by high levels of cholesterol in the blood. According to (Riskesdas) 2018, it shows 21.2% of the Indonesian population aged ≥ 15 years. Hypertension, type 2 diabetes mellitus (T2DM) and hypercholesterolemia are chronic disease disorders that are interrelated with each other due to overlapping risk factors such as endothelial dysfunction, vascular inflammation, arterial remodeling, atherosclerosis, dyslipidemia and obesity. There are many cardiovascular complications in diabetes and hypertension, especially related to microvascular and macrovascular diseases such as stroke, heart failure, kidney disease, retinopathy, neuropathy and amputation. To reduce morbidity and mortality rates, Evidence Based Medicine-based service management is carried out in patients by identifying risk factors, clinical problems, and patient management based on a patient problem-solving framework with a patient-centered, family-focused and community-oriented approach. This study is a case report. Primary data were obtained through anamnesis, physical examination and home visits to assess the physical environment. Assessment based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively.